Silver–N‐heterocyclic carbene complexes‐catalyzed multicomponent reactions: Synthesis, spectroscopic characterization, density functional theory calculations, and antibacterial study. Issue 9 (15th June 2021) - Mnasri, Aziza; Mejri, Amal; Al‐Hazmy, Sadeq M.; Arfaoui, Youssef; Özdemir, Ismail; Gürbüz, Nevin; Hamdi, Naceur
Abstract: Nowadays, silver– N ‐heterocyclic carbene (silver–NHCs) complexes are widely used in medicinal chemistry due to their low toxic nature toward humans. Due to the success of silver–NHCs in medicinal applications, interest in these compounds is rapidly increasing. Therefore, the interaction of N, N ‐disubstituted benzimidazolium salts with Ag2 O in dichloromethane to prepare novel Ag(I)–NHCs complexes was carried out at room temperature for 120 h in the absence of light. The obtained complexes were identified and characterized by 1 H and 13 C nuclear magnetic resonance, Fourier‐transform infrared, UV–Vis, and elemental analysis techniques. Then, the silver complexes were applied for three‐component coupling reactions of aldehydes, amines, and alkynes. The effect of changing the alkyl substituent on the NHCs ligand on the catalytic performance was investigated. In addition, it has been found that the complexes are antimicrobially active and show higher activity than the free ligand. The silver–carbene complexes showed antimicrobial activity against specified microorganisms with MIC values between 0.24 and 62.5 μg/ml. These results showed that the silver–NHC complexes exhibit an effective antimicrobial activity against bacterial and fungal strains. A density functional theory calculation study was performed to identify the stability of the obtained complexes. All geometries were optimized employing an effective core potential basis, such as LANL2DZ for the Ag atom and 6‐311+G(d, p) for all the other atoms in the gas phase. Electrostatic potential surfaces and LUMO–HOMO energy were computed. Transition energies and excited‐state structures were obtained from the time‐dependent density functional theory calculations. Abstract : Novel Ag(I)– N ‐heterocyclic carbene (NHCs) complexes were prepared and applied for three‐component coupling reactions of aldehydes, amines, and alkynes. The effect of changing the alkyl substituent on the NHCs ligand on the catalytic performance was investigated. The silver–NHC complexes showed effective antimicrobial activity against bacterial and fungal strains. A density functional theory calculation study was performed to identify the stability of the obtained complexes.